Comparison of cefotaxime and ofloxacin in treatment of spontaneous bacterial peritonitis - Bengür TAŞKIRAN; Önder ÇOLAKOĞLU; Bülent SÖZMEN; Belkıs ÜNSAL; Sakine L. ASLAN; Zafer BUYRAÇ (Turkish Journal of Gastroenterology, 2019)
-